2007
DOI: 10.1073/pnas.0604982104
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing tumor-promoting T cells in chemically induced cutaneous carcinogenesis

Abstract: There is a longstanding but poorly understood epidemiologic link between inflammation and cancer. Consistent with this, we previously showed that ␣␤ T cell deficiency can increase resistance to chemical carcinogenesis initiated by 7,12-dimethylbenz[a]anthracene and promoted by phorbol 12-myristate 13-acetate. This provoked the hypothesis that ␣␤ T cell deficiency removed T regulatory cells that limit the anti-tumor response or removed a specific tumor-promoting (T-pro) T cell population. Here we provide eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 29 publications
(34 reference statements)
3
62
1
2
Order By: Relevance
“…44 Interestingly, a T cell population with similar characteristics has also been detected in healthy human skin. 45 Thus, IFN-g might not always be supportive in terms of an effective tumor immune surveillance.…”
Section: Discussionmentioning
confidence: 91%
“…44 Interestingly, a T cell population with similar characteristics has also been detected in healthy human skin. 45 Thus, IFN-g might not always be supportive in terms of an effective tumor immune surveillance.…”
Section: Discussionmentioning
confidence: 91%
“…Much attention has been paid to the finding that tumor stromal cells and tumor-associated macrophages, in part by producing IL-23, mainly contribute to the induction of cancer by promoting inflammation, whereas T cells suppress tumor development as part of the immunosurveillance system [23][24][25][26][27][28][29]. Recent research has provided evidence for the involvement of T cells in promoting tumor progression [28][29][30][31][32][33][34][35]; however, the precise effects of T cells and the cytokines they produce on tumorigenesis remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been paid to the finding that tumor stromal cells and tumor-associated macrophages, in part by producing IL-23, mainly contribute to the induction of cancer by promoting inflammation, whereas T cells suppress tumor development as part of the immunosurveillance system [23][24][25][26][27][28][29]. Recent research has provided evidence for the involvement of T cells in promoting tumor progression [28][29][30][31][32][33][34][35]; however, the precise effects of T cells and the cytokines they produce on tumorigenesis remain controversial.In this paper, we demonstrate that (i) IL-17 is a pro-tumor cytokine, which supports tumor growth by promoting angiogenesis; (ii) gd T cells, but neither TCRabCD4 1 T cells nor TCRabCD8 1 T cells, are the major cellular source of IL-17 in tumor-infiltrating lymphocytes (TIL); (iii) blood circulating gd T cells, but not skin-resident Vg5 1 gd T cells, infiltrate into the tumor site; (iv) tumor-infiltrating gd T cells differentiate into IL-17-producing cells but downmodulate their cytotoxic activity within the tumor microenvironment; (v) IL-17 produced by tumor-infiltrating gd T cells promotes tumor progression by inducing angiogenesis. Thus, this paper proposes the novel concept that IL-17-producing gd T cells play a crucial role as tumor-promoting T cells during tumor development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, once a malignancy develops, immune cells, such as tumour-associated macrophages (TAMs), can also promote malignant cell growth by stimulating angiogenesis, invasion and metastasis [109], and high levels of TAMs are correlated with poor prognosis [110]. CD8þ and IFNÇ-producing helper T cells are also present frequently in the tumour microenvironment and they exert tumour and metastasis: promoting effects [111][112][113][114]. A recent study demonstrated that tumour-bearing mice had higher CSC-specific IgG levels in serum after vaccination with CSC lysate-activated dendritic cells (DCs).…”
Section: Immune Responsesmentioning
confidence: 99%